Modelling and simulation of the state of charge of battery management system in electric vehicle - Chan, Yong Hua (2016)
SOC, being the acronym for state of charge, is a vital indicator used by the BMS (Battery Monitoring System) that depicts the amount of charges or capacity left in a certain battery cell, before requiring charging or in some cases, discharging. Battery cells that are used in EVs (Electric Vehicles) requires many of such cells in series to form into a single complete battery pack that has enough power to drive a 3phase electrical motor, for long periods of time, typically measured in miles per hour. It is understood that cells in series will form a higher potential voltage, with the current flow limited by the single cell. It is often required for each cell to have as much energy stored as possible that can deliver as much power when needed, without compromising to the required operating voltages. While it is necessary to achieve voltages of 400~600Vdc and power, it makes little sense to control it at such high levels as it adds difficulty and danger in doing so. Instead, it is advisable to look into situations of lower voltage levels, typically in the range of 12~50Vdc, which is in this case, from a single battery cell. Modelling of a simple battery cell can be represented by passive components that create and forms the basic parameters that can be varied, in order to achieve the desired results. This report seeks to provide basic background knowledge and to highlight the importance of battery cells in electric vehicles and how it can accurately predict its performance with respect to its individualistic equivalent circuits. Use of MATLAB simulations are made in verifying the results.